Analisis Semiotik Dalam Film Kkn Desa Penari Karya Awi Suryadi Dan Implikasinya Dalam Pembelajaran Bahasa Indonesia - Sirina Olimpia; Alifiah Nurachmana; Indra Perdana; Yuliati Eka Asi; Ibnu Yustiya Ramadhan (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The purpose of this research is to describe (1). describes the markers in the KKN Desa Penari film (2). Describe the signified meaning in the KKN Desa Penari film, (3). Describe the myths resulting from signifiers and signifieds, and (4). Describe the implications of this research with learning Indonesian in schools. The method in this study uses a qualitative approach in collecting data using descriptive methods using Roland Barthes' theory which includes signifiers, signifieds and myths. Qualitative data were obtained from dialogue excerpts and screenshots taken from the film KKN Desa Penari. The results of this study show that (1) There are 19 data in the form of markers in the Penari Village KKN film (2) There are 19 data about the form and meaning of the sign in the Penari Village KKN film (3) The meaning of myths in the Dancer Village KKN film and (4) The implications in this study are adjusted to basic competencies 3.16 and 4.16 in grade VIII junior high school in odd semesters.